"The One Bright Spot": Presidential Personal Diplomacy and the Good Neighbor Policy. Issue 2 (4th February 2021) - Chavez, Tizoc
Abstract: In the 1930s and 1940s, personal diplomacy by U.S. presidents was still in its infancy, but it was central to the Good Neighbor policy in Latin America. To overcome years of mistrust, U.S. presidents, both at home and abroad, tried to personally convince their Latin American counterparts of their sincerity for more equitable relations. This article examines how Calvin Coolidge, Herbert Hoover, and especially Franklin Roosevelt used leader‐to‐leader diplomacy to change perceptions of the United States in Latin America and usher in a new era in hemispheric relations. The diplomacy of the Good Neighbor policy also had implications for the presidency, as it foreshadowed what would become standard practice for modern presidents.